Are there social spillovers in consumers' security assessments of payment instruments? - Charles M. Kahn; José M. Li\~nares-Zegarra; Joanna Stavins (Federal Reserve Bank of Boston, 2016)
Even though security of payments has long been identified as an important aspect of the consumer payment experience, recent literature fails to appropriately assess the extent of social spillovers among payment users. We test for the existence and importance of such spillovers by analyzing whether social influence affects consumers' perceptions of the security of payment instruments. Based on a 2008-2014 annual panel data survey of consumers, we find strong evidence of social spillovers in payment markets: others' perceptions of security of payment instruments exert a positive influence on one's own payment security perceptions. The significant and robust results imply that a consumer's assessments of security converge to his peers' average assessment: a 10 percent change in the divergence between one's own security rating and peers' average rating will result in a 7 percent change in one's own rating in the next period. The results are robust to many specifications and do not change when we control for actual fraud or crime data. Our results indicate that spillovers rather than reflection appear to be the cause, although separating the two causes is very difficult (Manski 1993). In particular, the spillovers are stronger for people who experience an exogenous shock to security perception, people who have more social interactions, and younger consumers, who are more likely to be influenced by social media. We also examine the effects of social spillovers on payment behavior (that is, on decisions regarding payment adoption and use). Our results indicate that social spillovers have a rather limited impact on payment behavior, as others' perceptions seem to affect one's own payment behavior mainly indirectly through the effect on one's own perceptions.
Keywords: D12; G02; G20; 330